2003
DOI: 10.1073/pnas.0836650100
|View full text |Cite
|
Sign up to set email alerts
|

Signal sequence within FcγRIIA controls calcium wave propagation patterns: Apparent role in phagolysosome fusion

Abstract: Calcium oscillations and traveling calcium waves have been observed in living cells, although amino acid sequences regulating wave directionality and downstream cell functions have not been reported. In this study we identify an amino acid sequence within the cytoplasmic domain of the leukocyte IgG receptor Fc␥RIIA that affects the amplitude of calcium spikes and the spatiotemporal dynamics of calcium waves in the vicinity of phagosomes. By using high-speed microscopy to map calcium-signaling routes within cel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
31
0

Year Published

2004
2004
2019
2019

Publication Types

Select...
6
1

Relationship

4
3

Authors

Journals

citations
Cited by 43 publications
(34 citation statements)
references
References 30 publications
3
31
0
Order By: Relevance
“…Using previously established quantitative microfluorometry and high-speed fluorescence microscopy methods, we have studied the Ca 2ϩ signaling events associated with spontaneous neutrophil motility. Using an efficient optical system and photodetector capable of sensing single atoms, we have been able to achieve electronic shutter speeds of ϳ0.1 s, which allows us to follow the intracellular trafficking of intracellular signals (10,12,13). Our recent study (10) and the experiments described above indicate that the plasma membrane component of this signal originates at the lipid raft-like lamellipodium.…”
Section: Discussionmentioning
confidence: 96%
See 2 more Smart Citations
“…Using previously established quantitative microfluorometry and high-speed fluorescence microscopy methods, we have studied the Ca 2ϩ signaling events associated with spontaneous neutrophil motility. Using an efficient optical system and photodetector capable of sensing single atoms, we have been able to achieve electronic shutter speeds of ϳ0.1 s, which allows us to follow the intracellular trafficking of intracellular signals (10,12,13). Our recent study (10) and the experiments described above indicate that the plasma membrane component of this signal originates at the lipid raft-like lamellipodium.…”
Section: Discussionmentioning
confidence: 96%
“…We have recently developed high-speed optical microscopy, which allows us to detect chemical signals within small cells with unprecedented detail (10,12,13). A previous high-speed microscopy study from this laboratory showed that each repetitive Ca 2ϩ spike corresponded to a Ca 2ϩ wave traveling around the neutrophil's periphery (10).…”
Section: M␤cd-sensitive L O Lipid Domains Are Required For Ca 2ϩ Wavementioning
confidence: 99%
See 1 more Smart Citation
“…The studies reported above provide some insight into the nature of Ca 2ϩ signaling associated with cell motility. On the basis of these and earlier (29,35) studies, we suggest that the initial Ca 2ϩ "flash" or "bump" is associated with the endoplasmic reticulum or a component of the endoplasmic reticulum closely associated with the plasma membrane. Alternatively, the TRP channel could be responding to cytoskeletal interactions or changes in membrane stress (63,64).…”
Section: Discussionmentioning
confidence: 99%
“…Our studies provide new insights into tumor cell migration and unprecedented detail concerning the cellular effects of Ca 2ϩ -active reagents on tumor cells. As we have emphasized (29,35,60), intracellular Ca 2ϩ waves, which are the Ca 2ϩ signal, can be very heterogeneous in their physical A final concentration of 25 g/ml fibronectin was added to the bottom chamber medium as a chemoattractant. After a 22-h incubation, transmigrated cells on the bottom side of the inserts were fixed, stained, and counted.…”
Section: Discussionmentioning
confidence: 99%